2012
DOI: 10.1259/bjr/74006772
|View full text |Cite
|
Sign up to set email alerts
|

Who's the doctor? Patients' perceptions of the role of the breast radiologist: a lesson for all radiologists

Abstract: Objective: The aim of this study was to explore patients' perceptions of the role of the radiologist in their care. Methods: The questionnaire used was designed in conjunction with a psychologist who had an interest in oncology, and piloted. The final questionnaires were distributed to patients attending the breast clinic at St James's Hospital, Dublin, Ireland, from 1 March to 1 July 2011. Patients requiring imaging (mammography and/or ultrasound) were asked to complete the same questionnaire again after imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 12 publications
4
20
0
Order By: Relevance
“…These in turn reduce unnecessary patient anxiety and worry. 28,29,32,33 The time saved thanks to a reduced occurrence of mistakes and delays can be utilised to address the individual needs of patients. 22,40 This improves the mammography experience, which, according to studies, has a great impact on mammography attendance rates.…”
Section: Efficacy Of Professional Teamworkmentioning
confidence: 99%
“…These in turn reduce unnecessary patient anxiety and worry. 28,29,32,33 The time saved thanks to a reduced occurrence of mistakes and delays can be utilised to address the individual needs of patients. 22,40 This improves the mammography experience, which, according to studies, has a great impact on mammography attendance rates.…”
Section: Efficacy Of Professional Teamworkmentioning
confidence: 99%
“…However, this paradigm has come at a cost: 50% of Americans are now uncertain whether a radiologist interprets or acquires imaging studies (13). One study found that only 14% of patients knew that radiologists were physicians; most believed that radiologists simply have a degree in radiography (13).…”
Section: Visibility To Clinicians and Patientsmentioning
confidence: 99%
“…Owing to the increasing diagnostic speed and volume of imaging procedures, radiologists face significant reporting burdens and consequently less time to interact with patients [1][2][3][4]. Perhaps not surprising but detrimental to our profession, it was found that 76% of the patients did not know what the role of a radiologist is, with some believing that "radiologists are the guys who ask patients if somebody had allergies" [5].…”
Section: Introductionmentioning
confidence: 99%